The interleukin 22 pathway interacts with mutant KRAS to promote poor prognosis in colon cancer. - McCuaig, S; Barras, D; Mann, E; Friedrich, M; Bullers, SJ; Janney, A; Garner, LC; Domingo, E; Koelzer, VH; Delorenzi, M; Tejpar, S; Maughan, TS; et al. (American Association for Cancer Research, 2020)
Purpose: The cytokine interleukin 22 (IL-22) promotes tumor progression in murine models of colorectal cancer (CRC). However, the clinical significance of IL-22 in human CRC remains unclear. We sought to determine whether the IL-22 pathway is associated with prognosis in human CRC, and to identify mechanisms by which IL-22 can influence disease progression. Experimental Design: Transcriptomic data from stage II/III colon cancers in independent discovery (GSE39582 population-based cohort, N=566) and verification (PETACC3 clinical trial, N=752) datasets were used to investigate the association between IL-22 receptor expression (encoded by the genes IL22RA1and IL10RB), tumor mutation status, and clinical outcome using Cox proportional hazard models. Functional interactions between IL-22 and mutant KRAS were elucidated using human CRC cell lines and primary tumor organoids. Results: Transcriptomic analysis revealed a poor-prognosis subset of tumors characterized by high expression of IL22RA1, the alpha subunit of the heterodimeric IL-22 receptor, and KRASmutation (RFS: HR=2.93, P=0.0006; OS: HR=2.45, P=0.0023). KRASmutations showed a similar interaction with IL10RB, and conferred the worst prognosis in tumors with high expression of both IL22RA1and IL10RB(RFS: HR=3.81, P=0.0036; OS: HR=3.90, P=0.0050). Analysis of human CRC cell lines and primary tumor organoids, including an isogenic cell line pair that differed only in KRASmutation status, showed that IL-22 and mutant KRAScooperatively enhance cancer cell proliferation, in part through augmentation of the Myc pathway. Conclusions: Interactions between KRASand IL-22 signaling may underlie a previously unrecognized subset of clinically aggressive CRC that could benefit from therapeutic modulation of the IL-22 pathway.